Asupan Kalsium, Asupan Vitamin C Dan Kejadian Konstipasi Pada Lansia Di Panti Wreda Bhakti Dharma Surakarta - AZALISTA, ITTAQ AMRI, Nur Lathifah Mardiyati, S.Gz., M.S, Dyah Widowati, SKM (2015)
Background: Constipation is the difficulty to defecate, which is due to a reduction in bowel movement function and stool movement difficulties. Beside the decreasing of gastrointestinal function, constipation in elderly is also affected by food consumption. Objective: This study aimed to analyse the dietary intakes of calcium and vitamin C and constipation in senior citizens at Bhakti Dharma Nursing Home Surakarta Research Methodology: This research used a descriptive study. The data collecting technique used observationand questionnaires. The subjects were 44 senior citizens at Bhakti Dharma Nursing Home of Surakarta.Thedata were taken usingcross-sectional method. Constipation data were collected from questionnaireswhile intakes of calcium and vitamin C were gotten through food record method. Results of Study: This study showed that the average consumption of calciumsubjects was 189,54 ± 34,4 mg,which was under the Recomended Nutrition Adequacy. The average consumption of vitamin C atthe subjectwas 48,9 ± 4,75 mg, which was under the Recomended Nutrition Adequacy. Conclusions:Constipation in senior citizens is not only affected by calcium and vitamin C intakes, but also medicine consumption, stress, inadequacy intakes, and liquid consumption. Keywords: constipation, calcium intake, intake of vitamin C Bibliography: 44 : (1996-2014)